2007
DOI: 10.1002/mame.200600275
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics and Phase Transformations During Cure of a Thermoplastic‐Modified Epoxy Thermoset

Abstract: A comprehensive thermal and rheological characterisation of a commercially important aerospace resin system modified with a thermoplastic toughener is presented here. The primary focus has been the understanding of how the cure kinetics and mechanism relate to other processes such as phase separation during cure. Differential scanning calorimetry has shown that thermoplastic modification does not affect the cure mechanism significantly and that the process was dominated by an autocatalytic process up to vitrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
3
18
1
Order By: Relevance
“…Δ H total was found to be 511 J/g. This value is similar to that reported by Varley [16]. The fractional residual epoxide conversion α t was converted to a percentage conversion at time t using the following equation: …”
Section: Materials and Experimental Proceduressupporting
confidence: 79%
See 2 more Smart Citations
“…Δ H total was found to be 511 J/g. This value is similar to that reported by Varley [16]. The fractional residual epoxide conversion α t was converted to a percentage conversion at time t using the following equation: …”
Section: Materials and Experimental Proceduressupporting
confidence: 79%
“…After gelation, the resin behaves like an elastic solid, and its shear modulus had increased by several orders of magnitude at vitrification (i.e., 10 MPa). Kinetic and rheometric data on isothermally cured RTM6 resin between 110°C and 180°C has previously been reported by Varley [16]. Varley reported gelation time varying with temperature from 358 min at 110°C to 18 min at 180°C.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…As the network formed however, a 10% strain may have been too large to ensure the newly formed structure was not disturbed, thus not obtaining as high a viscosity build up or storage modulus as one would otherwise have expected. Instrumental limitations disallowed a change in % strain while curing progressed, in order to obtain a full spectrum of the cure profile without structural compromization 48. The gel times established from the crossover of G ′ and G ″ in uni‐frequency mode at 1 Hz are displayed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, low viscosity would cause coalescence and rupture of bubbles during the blowing process. Figure 2 shows the steady shear viscosity of CE60 mixture resin system as a function of time, cured at temperature from 140 C to 180 C. It can be observed that the viscosity of the systems shows a similar tendency and possess an induction period 29,30 (where the increase in viscosity is modest and gradual, followed by an extremely rapid exponential increase in viscosity). The induction period in steady shear viscosity is about 53, 35, 22, and 17 min at 140, 150, 170, and 180 C, respectively, as seen in Figure 2.…”
Section: Resultsmentioning
confidence: 98%